2010
DOI: 10.2754/avb201079020169
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Muscle Fibre Types in Casertana Pig

Abstract: Little is known about the Casertana pig. The aim of this study was to evaluate the effect of sex on histochemical and morphometrical characteristics of muscle fibres (myocytes) in this pure breed and to verify the presence of giant fibres as well as vascularity of the muscle. Finally, maximum shortening velocity and isometric tension were measured in single muscle fibres.Sixteen Casertana pigs (8 males, 8 females) from a farm in Campania (Italy) were slaughtered at one year of age. Muscle tissues were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…In this research, in m. semitendinosus of slaughter pigs it were determined about 21 % of STO fi bers, 28 % of FTO fi bers and 52 % of FTG fi bers. The cross sectional area of different fi ber types in m. semitendinosus of slaughter pigs obtained in this study was 3800-4650 μm 2 , which is in accordance with results of [5] and [18].…”
Section: Discussionsupporting
confidence: 90%
“…In this research, in m. semitendinosus of slaughter pigs it were determined about 21 % of STO fi bers, 28 % of FTO fi bers and 52 % of FTG fi bers. The cross sectional area of different fi ber types in m. semitendinosus of slaughter pigs obtained in this study was 3800-4650 μm 2 , which is in accordance with results of [5] and [18].…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of histological structure of this muscle showed signifi cant differences due to gender. The average cross sectional area of muscle fi bers was larger in barrows than in gilts, but a statistically signifi cant difference (p<0.05) was determined only for FTO fi bers, which is in accordance with results of some authors [7][8][9], but contradictory to other authors [10][11][12]. An inverse relationship between the number and cross sectional area of muscle fi bers was obtained.…”
Section: Resultssupporting
confidence: 74%
“…Some authors [5,6] point out that gender has no infl uence on the distribution of different muscle fi ber types. Other authors [7][8][9] consider gender as a factor affecting the diameter of muscle fi bers, with gilts having fi bers of a smaller diameter compared to barrows. On the contrary, there are data indicating a larger diameter and fi ber girth in gilts compared to barrows [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Petersen et al (1998) and Velotto et al (2010) both reported capillary-to-fiber ratios that ranged from 0.90 to 1.50 for the psoas major, rhomboideus, and longissimus dorsi muscles. The current study found ratios that ranged from 1.44 to 2.21 for all locomotor muscles examined.…”
Section: Fiber Type Succinate Dehydrogenase and Capillary Densitymentioning
confidence: 99%